2011
DOI: 10.1165/rcmb.2010-0345oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nerve Growth Factor in Ozone-Induced Neural Responses in Early Postnatal Airway Development

Abstract: Airway neural plasticity contributes to the process of airway remodeling in response to airway irritants. However, the mechanisms of neural remodeling in the airways during the early postnatal period, when responses to airway irritation may be most sensitive, have not been characterized. This study used a rat model to examine a possible mechanism of ozone (O 3 )-induced neural hyperresponsiveness during a critical period of developmental, postnatal day (PD) 6, that may be mediated by the neurotrophin nerve gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…These data indicate that SS exposure during early postnatal life increases the level of NGF in lung. We reported recently that NGF was involved in mediating increased substance P expression in ferret airways (39) and that tracheal instillation of NGF during the early postnatal period enhances substance P innervation in rat airway (17). These findings, coupled with the current study, support the possibility that NGF serves as a signaling molecule during inflammatory events in the airways by regulating neuropeptide production.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These data indicate that SS exposure during early postnatal life increases the level of NGF in lung. We reported recently that NGF was involved in mediating increased substance P expression in ferret airways (39) and that tracheal instillation of NGF during the early postnatal period enhances substance P innervation in rat airway (17). These findings, coupled with the current study, support the possibility that NGF serves as a signaling molecule during inflammatory events in the airways by regulating neuropeptide production.…”
Section: Discussionsupporting
confidence: 87%
“…In an earlier report (40), we showed that airway methacholine responsiveness and SP innervation were increased on PD59 after SS exposure during the early postnatal period but not in the later period. In an entirely different model, Hunter et al (17) showed that ozone exposure in rat pups before PD15 resulted in enhanced SP innervation, but exposures at PD21 and PD28 did not increase SP innervation. Early life exposures to ozone and house dust mite antigen in monkeys also lead to long-lasting effects on airway innervation (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of recent studies have found that the Trk family of receptors (RTK class VII; Fig. 4) that are responsive to the neurotrophin family of growth factors (238) has novel, diverse roles in ASM, including enhancing [Ca 2ϩ ] i and contractility, particularly in the setting of inflammation (120,200,223,236,239,248,268,344). Neurotrophins such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) are well recognized in the nervous system for both long-term genomic effects on neuronal growth, differentiation, and survival (181), as well as nongenomic, rapid effects of enhancing [Ca 2ϩ ] i and neurotransmitter release (24,159).…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…However, the functional role of neurotrophins in the airway are still under investigation. Here, recent data suggest that NGF is released by airway nerves in response to irritants [e.g., ozone (120,322) or cigarette smoke (336)], allergens (346), and infectious agents (38) contributing to irritability and enhanced contractility. NGF can also be derived from airway epithelial cells, for example following viral or bacterial infections (38,222).…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…The NT, NGF, is increased in asthmatic airways (8) and affects the airway nerve system (9)(10)(11)(12). In mice, levels of NGF have been reported to be increased in infiltrating cells, epithelial cells, and airway smooth muscle after allergic inflammation (13), and is associated with enhanced allergic response (14,15) and airway remodeling (16).…”
Section: Clinical Relevancementioning
confidence: 99%